Print-and-Spray Electromechanical Metamaterials - Min, Taeho; Cheong, Euimin; Lee, Changryeol; Park, Donghyun; Kim, Baekgyeom; Rodrigue, Hugo; Koh, Je Sung; Lee, Dongwoo (Soft Robotics, 2022)
Many types of novel stretchable and conductive materials have been developed, but all exhibit a large increase in resistance upon stretching. In this article, the design and fabrication methods of two types of electromechanical metamaterials are presented, where the first has an invariant electrical resistance and the second has a decreasing electrical resistance upon elongation. The metamaterials can be fabricated by a few rapid and simple steps: a flexible polymer part is three-dimensional printed and sprayed with a conductive coating. Parametric optimization of the geometrical dimensions of the resistance invariant structure yielded a metamaterial with a nearly constant electrical resistance up to ∼1100% of tensile strain, whose behavior could be predicted using the finite element method. The second metamaterial had a resistance that reduced by as much as 38% over a displacement of 600 μm. The design principles of these new types of metamaterials can open new possibilities for high-performance soft robots and flexible electronics.
Keywords: 3-D printing; 3D-printing; Design method; Electrical resistances; Electromechanical metamaterial; Fabrication method; Flexible polymers; Simple++; Spray coating; Stretchability; 3D printing; electromechanical metamaterials; flexible electronics; spray coating; stretchability